Developing a theory of change methodology to support the evaluation of place-based systems change interventions to support child and adolescent mental health and well-being. (October 2022) - Doherty, Robyn; Quinn, Neil; Colson, Abigail; Tucker, Amy; Cameron, Julie
Over the past few years, levels of mental health problems among children and adolescents have risen alongside an increased demand for services, which has driven the demand for a transformative systems change in how child and adolescent mental health services are delivered. Theory of change methodology is a valuable approach for advancing systems change. This article describes the theory of change process to evaluate a strategic partnership approach to advancing systems change improvements in child and adolescent's mental health. This article describes the development and application of a theory of change methodology for these strategic partnerships, discussing the benefits derived from developing the theory of change and its use by the programme staff and evaluation team. This article also discusses the challenges and limitations of using this approach and recommendations for use more widely.